The Role of Emotional Intelligence and Problem Focused Coping on the Stress Level of Students in Bali Who Are Writing Their Thesis - Ratna Devy Winayanti; Zabrina Valeria Putri Zulfikar; Putu Riana Artyanti Putri; Ida Bagus Gde Agung Yoga Pramana; Ayu Rahmaditha Apsary; Ni Wayan Yuli Anggreni (Psikostudia : Jurnal Psikologi, 2024)
Thesis preparation is one of the things that has the potential to cause stress for final year students. The stress of thesis preparation is influenced by the ability of students to control their emotions when facing obstacles in the preparation of the thesis so that individuals can think clearly in looking at problems. Stress is also influenced by the way individuals perceive problems and plan problem-solving strategies in the thesis preparation process. This study aims to find out the role of emotional intelligence and problem focus coping on the stress level of students when writing a thesis. Data was collected from 129 students in Bali who were writing their thesis. The stress level scale, emotional intelligence scale, and problem focus coping scale were used to measure these variables. The results of multiple regression showed that emotional intelligence and problem focus coping could explain 47.2% of the stress variant of students who were working on their thesis. This research can provide information so that students can improve and maintain emotional intelligence and problem-focused coping to reduce stress levels in students who are preparing their thesis.Penyusunan skripsi merupakan salah satu hal yang berpotensi menimbulkan stres pada mahasiswa tingkat akhir. Stres penyusunan skripsi dipengaruhi oleh kemampuan mahasiswa untuk mengendalikan emosi pada saat menghadapi hambatan dalam penyusunan skripsi sehingga individu mampu untuk berpikir jernih dalam memandang permasalahan. Stres juga dipengaruhi oleh cara individu memandang permasalahan dan merancanakan strategi pemecahan masalah dalam proses penyusunan skripsi. Penelitian ini bertujuan untuk mengetahui peran kecerdasan emosional dan problem focus coping terhadap tingkat stres mahasiswa pada saat menulis skripsi. Data dikumpulkan dari 129 mahasiswa di Bali yang sedang menulis skripsi. Skala tingkat stres, skala kecerdasan emosional, dan skala problem focus coping digunakan untuk mengukur variabel-variabel tersebut. Hasil regresi berganda menunjukkan bahwa kecerdasan emosional dan problem focus coping dapat menjelaskan 47,2% varian tingkat stres mahasiswa yang sedang mengerjakan skripsi. Penelitian ini dapat memberikan informasi agar mahasiswa dapat meningkatkan dan mempertahan kecerdasan emosional serta problem focused coping untuk mengurangi tingkat stres pada mahasiswa yang sedang menyusun skripsi.